The relationship between social intelligence and emotional intelligence: a critical analysis - Odeh Alsawalqa, Dr. Rula (Opción, 2019)
This article aimed to examine the relationship between social intelligence and emotional intelligence via comparative qualitative research methods. As a result, people may not be able to categorize their feelings precisely when they face physiological changes in their bodies, or they may not be sure of the events that activate their feelings, so they must adhere to the cultural rules of emotions that must be revealed to others. The study concluded that emotion is an essential part of forming and shaping the concept of social intelligence, and social intelligence includes emotional intelligence but is broader and more general than it.